DIPHOS® nail for proximal humeral fractures: our experience with more than 190 procedures and surgical tips - Quattrini, Fabrizio; Ciatti, Corrado; Gattoni, Serena; Burgio, Valeria; Puma Pagliarello, Calogero; Rivera, Fabrizio; Maniscalco, Pietro (Acta Biomedica Atenei Parmensis, 2022)
Aim: evaluate the outcome of proximal humeral nailing over 5 years follow-up, focusing on possible complications. Secondary endpoint is the description and analysis of some technical notes to simplify surgical procedure. Materials and Methods: the cohort is composed by 194 fractures fixed with short nail. Neer Classification was used to assess the type of fracture; Deltoid Tuberosity Index (DTI) was applied to verify local bone quality. Follow-up with X-rays and orthopaedic evaluation was conducted on every operated subject. Results: mean follow up of the study was 25.4 months. We registered an average CMS score of 84.66 points for 2-parts fractures, 79.05 points for 3-part fractures and 68.62 points for 4-parts fractures. We obtained radiographical healing in 95.9% of patients (186/194) after 2.7 months on average. We recorded “very good” / “good” results in 90.3% of 2-parts fractures, 88.5% of 3-parts fractures and 46.2% of 4-part fractures. Overall complication rate was 10.3% (20/194 nails). Second surgery was performed in 8.2% (16/194) of cases. Conclusion: intramedullary nailing is an effective treatment for 2 and 3-part fractures with relatively low incidence of complications, small surgical accesses and short surgical time. Future researches are necessary to analyze the results related to nailing in 4-fragment fractures, still uncertain and influenced by multiple factors. The presence of the intramedullary nail reduces the lever arm of the screws making the osteosynthesis more reliable. Modern nails guarantee angular stability for proximal cancellous screws and allows 1 or 2 screws at calcar level to get a valid medial support.